VariantFoldRNA: a flexible, containerized, and scalable pipeline for genome-wide riboSNitch prediction - Kirven, Kobie J; Bevilacqua, Philip C; Assmann, Sarah M (NAR genomics and bioinformatics, 2025)
Single nucleotide polymorphisms (SNPs) can alter RNA structure by changing the proportions of existing conformations or leading to new conformations in the structural ensemble. Such structure-changing SNPs, or riboSNitches, have been associated with diseases in humans and climate adaptation in plants. While several computational tools are available for predicting whether an SNP is a riboSNitch, these tools were generally developed to analyze individual RNAs and are not optimized for genome-wide analyses. To fill this gap, we developed VariantFoldRNA, a flexible, containerized, and automated pipeline for genome-wide prediction of riboSNitches. Our pipeline automatically installs all dependencies, can be run locally or on high-performance clusters, and is modular, enabling the user to customize the analysis for the research question of interest. VariantFoldRNA can predict riboSNitches genome-wide at user-specified temperatures and splicing conditions, opening the door to novel analyses. The pipeline is an open-source command-line tool that is freely available at https://github.com/The-Bevilacqua-Lab/variantfoldrna.